Sensitive electrochemical immunosensor for matrix metalloproteinase-3 based on single-wall carbon nanotubes - Munge, Bernard S. (2010)
A novel electrochemical immunosensor for the detection of matrix metalloproteinase-3 (MMP-3), a cancer biomarker protein, based on vertically aligned single-wall carbon nanotube (SWCNT) arrays is presented. Detection was based on a sandwich immunoassay consisting of horseradish peroxidase (14–16 labels) conjugated to a secondary antibody and/or a polymer bead loaded with multi-enzyme labels. Performance was optimized by effective minimization of non-specific binding (NSB) events using Bovine serum albumin (BSA), Tween-20 and optimization of the primary antibody and secondary antibody concentrations. Results provided a detection limit of 0.4 ng mL(−1) (7.7 pM) for the 14–16 label sensor protocol and 4 pg mL(−1) (77 fM) using a multiply enzyme labeled polymeric bead amplification strategy in 10 μL of calf serum. This immunosensor based on SWCNT arrays offers great promise for a rapid, simple, cost-effective method for clinical screening of cancer biomarkers for point-of-care diagnosis.